A simulation-based approach to assess eco-process innovation performance - Suziyana, Mat Dahan; S. M., Yusof (IOP Publishing, 2019)
In the recent decade, eco-process innovation practice has been prioritised over other green strategies to help manufacturing firm becoming more sustainable. This paper evaluates the improvement in production cycle time as an outcome of the eco-process innovation, using the actual data of a manufacturing facility. Discrete event simulation approach was adopted to model and simulate the cycle time of previous state and current state of an eco-innovated production line. Result of cycle time per entity revealed a 6% reduction, thus proving that implementation of eco-process innovation could improve the economic performance of manufacturing firm. The study is a small part of a larger research work of which the authors are developing indicators for measuring eco-process innovation performance at firm level.